COACHING CLINIK LATIHAN BERTAHAN FUTSAL MIX DEFENCE PADA CLUB FUTSAL FERNANDO BSM U-19 BANJARBARU - Habibie, Muhammad; Kasanrawali, Andi; Fawaid, Muhammad (PT. Jurnal Center Indonesia Publisher, 2025)
Fernando BSM U-19 players continue to experience confusion in implementing defensive collaboration, which hinders their ability to execute defensive strategies effectively. This coaching clinic activity aims to facilitate coaches and players in understanding, implementing, and developing defensive system patterns, particularly mixed defense patterns in futsal. This community service was carried out through three meetings, beginning with a pre-test in the form of a questionnaire containing 15 questions regarding defensive pattern strategies. After the coaching clinic, a similar questionnaire was administered again as a post-test. The results of the activity showed an increase in understanding of up to 80% among players and coaches after participating in the training. This finding confirms that the coaching clinic method is able to deliver material systematically and easily understood, so it can be an effective alternative strategy in improving the understanding of defensive tactics in futsal.